A 13.5‐in. Quad‐FHD Flexible CAAC‐OS AMOLED Display with Long‐Life OLED Device Structure. Issue 1 (June 2014) - Uesaka, Shogo; Yamaoka, Ryohei; Sasaki, Toshiki; Chida, Akihiro; Kawashima, Susumu; Isa, Toshiyuki; Seo, Satoshi; Hirakata, Yoshiharu; Yatsuzuka, Shota; Ohide, Takayuki; Nakata, Masataka; Yamazaki, Shunpei; et al.
Abstract In this study, the device structure of a white tandem OLED is changed to control the emission area to achieve less luminance decay. A long‐life 13.5‐inch 4K flexible CAAC‐OS AMOLED with less color shift and high resolution is fabricated using this long‐life white OLED, transfer technology, and a CAAC‐OS FET.